A Protochlorophyllide (Pchlide) a Oxygenase for Plant Viability - Reinbothe, Steffen; Bartsch, Sandra; Rossig, Claudia; Davis, Manli Yang; Yuan, Shu; Reinbothe, Christiane; Gray, John (Frontiers in Plant Science, 2019)
Higher plants contain a small, 5-member family of Rieske non-heme oxygenases that comprise the inner plastid envelope protein TIC55, phaeophorbide a oxygenasee (PAO), chlorophyllide a oxygenase (CAO), choline monooxygenase, and a 52 kDa protein (PTC52) associated with the precursor NADPH:protochlorophyllide (Pchlide) oxidoreductase A (pPORA) A translocon (PTC). Some of these chloroplast proteins have documented roles in chlorophyll biosynthesis (CAO) and degradation (PAO and TIC55), whereas the function of PTC52 remains unresolved. Biochemical evidence provided here identifies PTC52 as Pchlide a oxygenase of the inner plastid envelope linking Pchlide b synthesis to pPORA import. Protochlorophyllide b is the preferred substrate of PORA and its lack no longer allows pPORA import. The Pchlide b-dependent import pathway of pPORA thus operates in etiolated seedlings and is switched off during greening. Using dexamethasone-induced RNA interference (RNAi) we tested if PTC52 is involved in controlling both, pPORA import and Pchlide homeostasis in planta. As shown here, RNAi plants deprived of PTC52 transcript and PTC52 protein were unable to import pPORA and died as a result of excess Pchlide a accumulation causing singlet oxygen formation during greening. In genetic studies, no homozygous ptc52 knock-out mutants could be obtained presumably as a result of embryo lethality, suggesting a role for PTC52 in the initial greening of plant embryos. Phylogenetic studies identified PTC52-like genes amongst unicellular photosynthetic bacteria and higher plants, suggesting that the biochemical function associated with PTC52 may have an ancient evolutionary origin. PTC52 also harbours conserved motifs with bacterial oxygenases such as the terminal oxygenase component of 3-ketosteroid 9-alpha-hydroxylase (KshA) from Rhodococcus rhodochrous. 3D-modelling of PTC52 structure permitted the prediction of amino acid residues that contribute to the substrate specificity of this enzyme. In vitro-mutagenesis was used to test the predicted PTC52 model and provide insights into the reaction mechanism of this Rieske non-heme oxygenase.